UPAYA MENINGKATAN KOMPETENSI GURU DALAM PELAKSANAAN PROSES PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI SD NEGERI 017 PASIR EMAS - Dana Rasmita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research was motivated by the many weaknesses encountered especially in the implementation of the learning process carried out by teachers at the 017 Golden Sand Public Elementary School. The strategy used to help teachers improve teacher competency in the implementation of the learning process by intensifying the implementation of academic supervision. The aim is to improve the process of implementing learning carried out by teachers in the classroom. The results showed, where the average value of teachers in the learning process cycle I was 72.85 with sufficient categories. After the second cycle, the value of teacher competence in the process of learning has increased to 88.00 with a very good category. This proves that, through academic supervision, it can improve teacher competence in the implementation of the learning process at 017 Golden Sand Public Elementary School.